2011
DOI: 10.1128/jvi.02539-10
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Human Endogenous Retrovirus (HERV) Group HML-2/HERV-K Does Not Depend on Canonical Promoter Elements but Is Regulated by Transcription Factors Sp1 and Sp3

Abstract: After fixation in the human genome, human endogenous retroviruses (HERVs) are bona fide cellular genes despite their exogenous origin. To be able to spread within the germ line and the early embryo, the ancient retroviral promoters must have adapted to the requirements for expression in these cell types. We describe that in contrast to the case for current exogenous retroviruses, which replicate in specific somatic cells, the long terminal repeat (LTR) of the human endogenous retrovirus HERV-K acts as a TATA-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 65 publications
2
79
0
Order By: Relevance
“…Early studies have suggested that expression of ubiquitous transcription factors such as Sp1, Myb, and YY1 proteins can stimulate transcription of HERVs from hypomethylated LTRs that contain essential binding sites (23–25). Recent data corroborated these observations by providing evidence that the HERV-K promoter activity is dependent on Sp1 and Sp3 transcription factors (26). Using chromatin immunoprecipitation (ChIP) and RNA interference assays, the binding of transcription factors Sp1 and Sp3 to the examined LTR promoter region of HERV-K was shown.…”
Section: Herv Reactivation In Cancermentioning
confidence: 76%
“…Early studies have suggested that expression of ubiquitous transcription factors such as Sp1, Myb, and YY1 proteins can stimulate transcription of HERVs from hypomethylated LTRs that contain essential binding sites (23–25). Recent data corroborated these observations by providing evidence that the HERV-K promoter activity is dependent on Sp1 and Sp3 transcription factors (26). Using chromatin immunoprecipitation (ChIP) and RNA interference assays, the binding of transcription factors Sp1 and Sp3 to the examined LTR promoter region of HERV-K was shown.…”
Section: Herv Reactivation In Cancermentioning
confidence: 76%
“…Such a mode of proviral DNA transcription is a basis of the HERV life cycle that provides the possibility of template jumps during proviral RNA reverse transcription. Further studies confirmed the prevailing activity of a non-canonical HERV-K/ HML-2 (ERVK) LTR promoter and showed it is regulated by Sp1 and Sp3 transcription factors via a TATA boxindependent transcription initiation mechanism [229]. A shift of the transcriptional start site can be explained by the initial adaptation to the human genomic context, which can be an early step in the complex process of the HERV sequence domestication and reshaping by the host genome.…”
Section: Impact On Human Evolutionmentioning
confidence: 84%
“…Fuchs et al reported that the HERV-K transcription is mediated by the transcription factors Sp1 and Sp3 which are upregulated during oxidative stress and cause the gene regulation controlling multiple cellular process, like DNA damage, chromatin remodeling and proliferation, differentiation, and apoptosis of cell [35]. The long terminal repeat (LTR) of HERV-K plays a role of a TATA- and initiator element-independent promoter which has a variable transcription start site and contains four G-rich stretches playing a role of nucleosome free binding regions for Sp1 and Sp3 [35]. The increased expression of HERV-K is related to malignancies, especially hormone-associated cancers.…”
Section: Discussionmentioning
confidence: 99%